Clinician consensus on "Inappropriate" presentations to the Emergency Department in the Better Data, Better Planning (BDBP) census: a cross-sectional multi-centre study of emergency department utilisation in Ireland - Niamh M Cummins; Louise A Barry; Carrie Garavan; Collette Devlin; Gillian Corey; Fergal Cummins; Damien Ryan; Emma Wallace; Conor Deasy; Mary Flynn; Gerard McCarthy; BDBP Team; et al. (BMC, 2023)
Abstract Background Utilisation of the Emergency Department (ED) for non-urgent care increases demand for services, therefore reducing inappropriate or avoidable attendances is an important area for intervention in prevention of ED crowding. This study aims to develop a consensus between clinicians across care settings about the "appropriateness" of attendances to the ED in Ireland. Methods The Better Data, Better Planning study was a multi-centre, cross-sectional study investigating factors influencing ED utilisation in Ireland. Data was compiled in patient summary files which were assessed for measures of appropriateness by an academic General Practitioner (GP) and academic Emergency Medicine Consultant (EMC) National Panel. In cases where consensus was not reached charts were assessed by an Independent Review Panel (IRP). At each site all files were autonomously assessed by local GP-EMC panels. Results The National Panel determined that 11% (GP) to 38% (EMC) of n = 306 lower acuity presentations could be treated by a GP within 24-48 h (k = 0.259; p < 0.001) and that 18% (GP) to 35% (EMC) of attendances could be considered "inappropriate" (k = 0.341; p < 0.001). For attendances deemed "appropriate" the admission rate was 47% compared to 0% for "inappropriate" attendees. There was no consensus on 45% of charts (n = 136). Subset analysis by the IRP determined that consensus for appropriate attendances ranged from 0 to 59% and for inappropriate attendances ranged from 0 to 29%. For the Local Panel review (n = 306) consensus on appropriateness ranged from 40 to 76% across ED sites. Conclusions Multidisciplinary clinicians agree that "inappropriate" use of the ED in Ireland is an issue. However, obtaining consensus on appropriateness of attendance is challenging and there was a significant cohort of complex heterogenous presentations where agreement could not be reached by clinicians in this study. This research again demonstrates the complexity of ED crowding, the introduction of evidence-based care pathways targeting avoidable presentations may serve to alleviate the problem in our EDs.